Analysis of the relationship between environmental literacy and pro-environmental attitudes of prospective biology teacher students at UIN Raden Mas Said Surakarta - Amining Rahmasiwi; Rahdatu Cahya Puranita; Salma Azzahro Rahayu (Universitas Negeri Yogyakarta, 2026)
Every biology teacher should have a pro-environmental attitude to integrate sustainability values into their teaching, but in reality, students do not consistently demonstrate this attitude. The purpose of this study was to determine the levels of environmental literacy and pro-environmental attitudes, and the relationship between these two variables, among biology teacher students at UIN Raden Mas Said Surakarta, class of 2024. A quantitative approach with a correlational method was used to analyze the relationship between the two variables. This study involved 36 participants, biology teacher students at UIN Raden Mas Said Surakarta, class of 2024. Data were obtained via a questionnaire on environmental literacy and pro-environmental attitudes and analyzed using descriptive statistics and inferential correlation tests. The results showed that students’ levels of environmental literacy and pro-environmental attitudes were generally positive. The correlation test showed a very strong and significant positive relationship between environmental literacy and pro-environmental attitudes (r = 0.828; p 0.05). This finding indicates that the higher students’ environmental literacy, the more pro-environmental attitudes they showed. Thus, environmental literacy is an important factor in fostering pro-environmental attitudes among prospective biology teacher students, so its strengthening needs to be integrated continuously into the prospective teacher education process.